Vanadium sodium fluorophosphate positive electrode material, preparation method and sodium ion battery
By using complex precipitant and anti-solvent regulation reaction system under room temperature and normal pressure, the problem of high-temperature preparation of sodium vanadium fluorophosphate positive electrode material is solved, high crystallinity and low-cost preparation are achieved, and its sodium ion battery is improved. electrochemical properties in.
Patent Information
- Application Number
- CN202411006792.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-25
- Publication Date
- 2024-12-27
AI Technical Summary
The existing high-temperature preparation method of sodium vanadium fluorophosphate positive electrode material leads to vanadium volatility, impurity of products, high energy consumption, high cost and poor crystallinity, which limits its application in sodium ion batteries.
By adding complex precipitant and anti-solvent to the room temperature and normal pressure aqueous solution, the supersaturation and solubility of the reaction system can be adjusted to achieve high crystallinity preparation of sodium vanadium fluorine phosphate and avoid the high-temperature sintering process.
It significantly reduces the energy consumption and cost of preparation, improves the crystallinity and electrochemical properties of sodium vanadium fluorophosphate, is suitable for industrial production, and is suitable for sodium ion battery positive electrode material.
Smart Images

Figure CN119191249A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a sodium vanadium fluorophosphate positive electrode material, a preparation method and a sodium ion battery, belonging to the technical field of sodium ion batteries. Background Art
[0002] In order to reduce greenhouse gas emissions, respond to climate change and promote sustainable development, the development of clean energy and energy storage technology has become a top priority. As a key way of energy conversion and utilization, energy storage technology is of great significance for balancing the power system, improving energy efficiency and promoting the large-scale application of renewable energy. Electrochemical energy storage, as an important energy storage technology, has received extensive attention and research in recent years. Among them, lithium-ion batteries, as one of the most common and mature electrochemical energy storage devices, have made significant progress in the fields of electric vehicles and renewable energy storage. However, they are currently facing problems such as insufficient and uneven distribution of lithium resources, which poses a challenge to the sustainable development of lithium-ion batteries. In order to overcome the resource limitations faced by lithium-ion batteries, researchers have begun to actively explore other feasible energy storage solutions. As a highly-regarded energy storage technology, sodium-ion batteries have become a potential candidate to replace lithium-ion batteries because of their abundant sodium resources and relatively low cost. Sodium-ion batteries have similar working principles to lithium-ion batteries, so they have great potential in the field of electrochemical energy storage.
[0003] The positive electrode material directly determines the energy density, cycle life and other properties of sodium ion batteries. Therefore, the selection of matching positive electrode materials has an important impact on the performance and application of sodium ion batteries. There are three main types of positive electrode materials for sodium ion batteries: transition metal oxides, Prussian blue (white) compounds, and polyanion compounds. In terms of the application needs of the energy storage market, the polyanion positive electrode material system has more advantages in raw material resource utilization, processing, safety, and cycle life. Among them, sodium vanadium fluorophosphate, as a vanadium-based polyanion positive electrode material, has an open three-dimensional host skeleton and a strong inductive effect, and usually exhibits superior long-cycle stability. However, the high preparation cost based on the synthesis strategy limits the scale-up production of sodium vanadium fluorophosphate. At present, the synthesis of sodium vanadium fluorophosphate mainly adopts high-temperature solid phase method, sol-gel method, and solvothermal method. If the preparation process includes a high-temperature sintering step, it will cause a large amount of vanadium to volatilize, making the product impure, and ultimately leading to poor electrochemical performance. Moreover, due to the high synthesis temperature, the energy consumption is extremely large, the preparation cost is high, and the product generally has no regular morphology, which is not conducive to the realization of high energy density. In addition, the hydrogen fluoride produced during the sintering process will corrode the equipment at high temperatures, further increasing the production cost. Therefore, using low-temperature preparation methods instead of traditional high-temperature strategies is an important means to obtain high-purity, low-cost sodium vanadium fluorophosphate positive electrode materials.
[0004] CN107154493A realizes the direct synthesis of sodium vanadium fluorophosphate in normal pressure aqueous solution by means of pre-reaction-precipitation reaction and the combined control of precipitation temperature and pH. However, the preferred temperature in the pre-reaction stage is 65-75°C, and the preferred temperature in the precipitation reaction stage still needs to be maintained above 85°C, resulting in high energy consumption for preparation. In addition, the crystallinity of the obtained product is relatively poor, resulting in poor electrochemical performance of the assembled battery, which limits its practical application.
[0005] CN116216689A achieves direct synthesis of sodium vanadium fluorophosphate in normal pressure aqueous solution by slowly adding a complexing precipitant into the raw material solution system, and the obtained product has good crystallinity. However, the reaction process temperature is relatively high (60-120°C), and it takes a long time to obtain the product of the same quality, and further improvement is needed in practical application. Summary of the invention
[0006] In view of this, the object of the present invention is to provide a sodium vanadium fluorophosphate positive electrode material, a preparation method and a sodium ion battery.
[0007] To achieve the above objectives, the technical solution of the present invention is as follows.
[0008] A method for preparing a sodium vanadium fluorophosphate positive electrode material, the method steps comprising:
[0009] (1) mixing a vanadium source, a sodium source, a phosphate source, a fluorine source and deionized water to obtain a mixed solution;
[0010] (2) adding the complexing precipitant to the mixed solution at a uniform rate within 0.5 to 2 hours, and then adding the anti-solvent at a uniform rate within 10 to 90 minutes. After the addition is completed, the solid-liquid separation, washing, and drying are performed to obtain a sodium vanadium fluorophosphate positive electrode material;
[0011] Wherein, the molar ratio of Na, V, P and F elements in the mixed solution is 3-15:2:2-15:1-15;
[0012] The molar ratio of the complexing precipitant to the vanadium source is 0.5 to 5:1;
[0013] The complexing precipitant is one or more of sodium glutamate, ammonia water, sodium tartrate and sodium lactate;
[0014] The anti-solvent is one or more of methanol, ethanol, propanol and isopropanol;
[0015] The molar ratio of the complexing precipitant to the anti-solvent is 100-250:2-5.
[0016] Preferably, in step (1), the vanadium source includes one or more of vanadium dioxide, vanadium oxychloride, vanadium oxysulfate, vanadium trioxide and vanadium trichloride.
[0017] Preferably, in step (1), the sodium source includes one or more of sodium fluoride, sodium dihydrogen phosphate, disodium hydrogen phosphate and sodium chloride.
[0018] Preferably, in step (1), the phosphate source includes one or more of phosphoric acid, sodium dihydrogen phosphate, ammonium dihydrogen phosphate, disodium hydrogen phosphate and diammonium hydrogen phosphate.
[0019] Preferably, in step (1), the fluorine source comprises sodium fluoride and / or ammonium fluoride.
[0020] Preferably, in step (2), the combination of the complexing precipitant and the anti-solvent is ammonia water and isopropanol, sodium glutamate and ethanol, sodium lactate and methanol.
[0021] Preferably, in step (2), the molar ratio of the complexing precipitant to the anti-solvent is 160-200:4-5.
[0022] Preferably, in step (2), the complexing precipitant is added to the mixed solution at a uniform rate within 1 to 1.5 hours, and then the anti-solvent is added within 40 to 60 minutes.
[0023] Preferably, in step (2), the pH of the solution is 4 to 6 after the anti-solvent is added.
[0024] The sodium vanadium fluorophosphate positive electrode material of the present invention is prepared by the above method, and the chemical formula is Na3(VO 1-x PO4)2F 1+2x , where 0≤x≤1.
[0025] A sodium ion battery comprises a positive electrode sheet made of the sodium vanadium fluorophosphate positive electrode material described in the present invention, a diaphragm, an electrolyte and a negative electrode sheet.
[0026] Preferably, the diaphragm is glass fiber.
[0027] Preferably, the electrolyte is an ester electrolyte.
[0028] Preferably, the negative electrode sheet is a metal sodium sheet.
[0029] Beneficial Effects
[0030] The present invention provides a method for preparing a sodium vanadium fluorophosphate positive electrode material. By adding a complexing precipitant, the controlled release of vanadium ions and phosphate radicals is achieved, so that the vanadium concentration and phosphate radical concentration in the reaction system are initially accumulated, thereby increasing the initial supersaturation of the system. Supersaturation is the driving force for crystal nucleation and growth. Therefore, increasing the supersaturation can effectively promote the crystal nucleation and growth process. However, this supersaturation is still not enough to achieve the precipitation of sodium vanadium fluorophosphate crystals under room temperature and normal pressure conditions. To this end, the present invention introduces an anti-solvent (poor solvent) that is miscible with the solvent but cannot dissolve the solute to reduce the solubility of the solute (product) in the solution, further increase the supersaturation, and finally achieve the precipitation of the product. The synergistic effect between the complexing precipitant and the anti-solvent realizes the reconstruction of the hydrogen bond network in the solution, and forms a local hydrophobic environment around the reactant ions, effectively weakening the electrostatic interaction between water molecules and reactant ions, weakening the shielding effect, and being more conducive to the accumulation of crystal nuclei. The present invention optimizes the ratio and addition time of the complexing precipitant and the anti-solvent, continuously improves the nucleation and growth dynamics in the synthesis process, and finally successfully prepares a high-crystallinity sodium vanadium fluorophosphate material under room temperature and normal pressure conditions. While ensuring a high conversion rate of the product, the preparation time is significantly improved, the energy consumption is reduced, and the production and preparation cost is greatly reduced, which is suitable for industrial production.
[0031] The present invention can quickly prepare sodium vanadium fluorophosphate in an aqueous solution at room temperature and normal pressure, without the need for subsequent aging treatment and high-temperature sintering processes, greatly reducing product energy consumption, shortening preparation time, and saving production costs. The prepared sodium vanadium fluorophosphate has high crystallinity and high yield, and is particularly suitable for use as a positive electrode material for sodium ion batteries, and the assembled battery exhibits excellent electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is the X-ray diffraction (XRD) diagram of the sodium vanadium fluorophosphate positive electrode material described in Example 1.
[0033] Figure 2 This is a scanning electron microscope (SEM) image of the sodium vanadium fluorophosphate positive electrode material described in Example 1.
[0034] Figure 3 1 is the charge and discharge curve of the sodium ion battery assembled in Example 1.
[0035] Figure 4 This is the XRD diagram of the sodium vanadium fluorophosphate positive electrode material described in Example 2.
[0036] Figure 5 This is the SEM image of the sodium vanadium fluorophosphate positive electrode material described in Example 2.
[0037] Figure 6 2 is the charge and discharge curve of the sodium ion battery assembled in Example 2.
[0038] Figure 7 This is the XRD diagram of the sodium vanadium fluorophosphate positive electrode material described in Example 3.
[0039] Figure 8 This is the SEM image of the sodium vanadium fluorophosphate positive electrode material described in Example 3.
[0040] Fig. 9 3 is the charge and discharge curve of the sodium ion battery assembled in Example 3.
[0041] Fig.10 This is the XRD pattern of the final product obtained in Comparative Example 1.
[0042] Fig.11 This is the SEM image of the final product obtained in Comparative Example 1.
[0043] Fig.12 This is the XRD pattern of the final product obtained in Comparative Example 2.
[0044] Fig.13 This is the SEM image of the final product obtained in Comparative Example 2. DETAILED DESCRIPTION
[0045] The present invention will be further described in detail below in conjunction with specific embodiments.
[0046] A method for preparing a sodium vanadium fluorophosphate positive electrode material, the method steps comprising:
[0047] (1) mixing a vanadium source, a sodium source, a phosphate source, a fluorine source and deionized water to obtain a mixed solution;
[0048] (2) adding the complexing precipitant to the mixed solution at a uniform rate within 0.5 h to 2 h, and then adding the anti-solvent at a uniform rate within 10 min to 1.5 h. After the addition is completed, the solid-liquid separation, washing, and drying are performed to obtain a sodium vanadium fluorophosphate positive electrode material;
[0049] Wherein, the molar ratio of Na, V, P and F elements in the mixed solution is 3-15:2:2-15:1-15;
[0050] The molar ratio of the complexing precipitant to the vanadium source is 0.5 to 5:1;
[0051] The complexing precipitant is one or more of sodium glutamate, ammonia water, sodium tartrate and sodium lactate;
[0052] The anti-solvent is one or more of methanol, ethanol, propanol and isopropanol;
[0053] The molar ratio of the complexing precipitant to the anti-solvent is 100-250:2-5.
[0054] In some embodiments, in step (1), the vanadium source is a trivalent or tetravalent vanadium source, including one or more of vanadium dioxide, vanadium oxychloride, vanadium oxysulfate (or its hydrate), vanadium trioxide and vanadium trichloride.
[0055] In some embodiments, a trivalent or tetravalent vanadium source can be obtained by reducing a pentavalent vanadium source. The reducing agent includes at least one of oxalic acid, ascorbic acid, tartaric acid, lactic acid, sodium ascorbate, sodium tartrate, sodium lactate, thiourea, sodium sulfite and sodium thiosulfate. The pentavalent vanadium source includes at least one of vanadium pentoxide, ammonium metavanadate and sodium metavanadate. The molar ratio of the pentavalent vanadium source to the reducing agent can be 1:0.5-5; after the aqueous solutions of the two are mixed, the reaction is carried out at a temperature of 60-90°C, for example 80°C; the reaction time can be 0.5-1h.
[0056] In some embodiments, in step (1), the sodium source includes one or more of sodium fluoride, sodium dihydrogen phosphate (or its hydrate), disodium hydrogen phosphate (or its hydrate) and sodium chloride.
[0057] In some embodiments, in step (1), the phosphate source includes one or more of phosphoric acid, sodium dihydrogen phosphate (or its hydrate), ammonium dihydrogen phosphate, disodium hydrogen phosphate (or its hydrate) and diammonium hydrogen phosphate.
[0058] In some embodiments, in step (1), the fluorine source includes sodium fluoride and / or ammonium fluoride.
[0059] In some embodiments, in step (2), the combination of the complexing precipitant and the anti-solvent is ammonia water and isopropanol, sodium glutamate and ethanol, sodium lactate and methanol, and more preferably sodium glutamate and ethanol.
[0060] In some embodiments, in step (2), the molar ratio of the complexing precipitant to the anti-solvent is 160-200:4-5.
[0061] In some embodiments, in step (2), the pH of the solution is 4-6 after the anti-solvent is added.
[0062] The sodium vanadium fluorophosphate positive electrode material of the present invention is prepared by the above method, and the chemical formula is Na3(VO 1-x PO4)2F 1+2x , where 0≤x≤1.
[0063] A sodium ion battery comprises a positive electrode sheet made of the sodium vanadium fluorophosphate positive electrode material described in the present invention, a diaphragm, an electrolyte and a negative electrode sheet.
[0064] In some embodiments, the membrane is fiberglass.
[0065] In some embodiments, the electrolyte is an ester electrolyte, comprising sodium perchlorate and sodium hexafluorophosphate as sodium salts, ethylene carbonate, propylene carbonate and diethyl carbonate as organic solvents, and fluoroethylene carbonate as an additive.
[0066] In some embodiments, the negative electrode sheet is a metal sodium sheet.
[0067] Example 1
[0068] Dissolve 1.141g of vanadium sulfate in 100mL of deionized water and stir evenly to obtain a vanadium source solution; add 3.276g of sodium dihydrogen phosphate dihydrate and 0.5g of sodium fluoride to the above vanadium source solution and stir evenly. Dissolve 7.098g of sodium glutamate in 100mL of deionized water, stir and dissolve evenly, and then add it to the above mixed solution at a uniform speed for 1h. During this process, the solution gradually changes from clear and transparent to turbid, but no obvious precipitation is observed at the bottom. After that, 100mL of ethanol is added to the above turbid solution at a uniform speed for 1h. During this process, the upper layer gradually begins to become clear and transparent, and light green precipitation begins to appear at the bottom and gradually increases; after the addition of ethanol is completed, the upper layer is almost completely colorless, clear and transparent, and a large amount of light green precipitation appears at the bottom. The above precipitate is washed 3 times with deionized water and ethanol respectively, and then vacuum dried at 60℃ for 8h to obtain 1.416g of product with a yield of 98.2%.
[0069] The obtained light green powder was subjected to XRD test, and the test results were as follows: Figure 1 The XRD results show that the product is Na3V2O2(PO4)2F, which has good crystallinity and high purity. The product was tested by scanning electron microscopy (SEM), and the test results are as follows Figure 2 The SEM results show that the prepared sodium vanadium fluorophosphate crystals are large block particles rather than flocculent particles, which further proves the high crystallinity of the product.
[0070] The obtained product Na3V2O2(PO4)2F was made into the positive electrode, and the metal sodium sheet was used as the negative electrode to assemble the button battery. The charge and discharge curve was tested at a current density of 0.1C. The test results are as follows: Figure 3 The test results show that the material has two discharge platforms near 4.0V and 3.60V voltages, the discharge capacity at 0.1C current density is 129.8mAh / g, and the discharge capacity at 0.2C current density is 126.2mAh / g, indicating that it has excellent electrochemical properties.
[0071] Example 2
[0072] Dissolve 0.819g of ammonium metavanadate and 1.26g of oxalic acid in 100mL of deionized water, heat to 80℃, stir at constant temperature for 0.5h, and stop heating; add 3.276g of sodium dihydrogen phosphate dihydrate and 0.5g of sodium fluoride to the above solution and stir evenly; dissolve 6.111g of sodium tartrate in 100mL of deionized water, stir and dissolve evenly, and then add it to the above mixed solution at a uniform speed, and the addition time is 1h. After that, add 100mL of propanol to the above turbid liquid at a uniform speed, and the addition time is 1h. After the addition is completed, a light green precipitate is obtained at the bottom layer, and the upper liquid is almost colorless, clear and transparent; wash the above precipitate with deionized water and ethanol 3 times each, and then vacuum dry it at 60℃ for 8h to obtain 1.393g of product with a yield of 96.6%.
[0073] The obtained light green powder was subjected to XRD test, and the test results were as follows: Figure 4 As shown. XRD results show that the product is Na3V2O2(PO4)2F, with good crystallinity and high purity. SEM test was performed on the product, and the test results are as follows Figure 5 The SEM results show that the prepared sodium vanadium fluorophosphate crystals have regular and uniformly distributed particles, smooth surfaces and clear grain boundaries, which clearly proves the high crystallinity of the product.
[0074] The obtained product Na3V2O2(PO4)2F was made into the positive electrode, and the metal sodium sheet was used as the negative electrode. The button battery was assembled to test its charge and discharge curve. The test results are as follows Figure 6 The test results show that the material has two discharge platforms near 4.0V and 3.60V voltages, the discharge capacity at 0.1C current density is 128.1mAh / g, and the discharge capacity at 0.2C current density is 124.7mAh / g, indicating that it has excellent electrochemical properties.
[0075] Example 3
[0076] Dissolve 1.274g of vanadium pentoxide and 0.62g of oxalic acid in 100mL of deionized water, heat to 90℃, stir at constant temperature for 0.5h, and stop heating; add 6.552g of sodium dihydrogen phosphate dihydrate and 1g of sodium fluoride to the above solution and stir evenly; dissolve 9.408g of sodium lactate in 100mL of deionized water, stir and dissolve evenly, and then add it to the above mixed solution at a uniform speed, and the addition time is 1h. After that, add 100mL of isopropanol to the above turbid liquid at a uniform speed, and the addition time is 1h. After the addition is completed, a light green precipitate is obtained at the bottom layer, and the upper liquid is almost colorless, clear and transparent; wash the above precipitate with deionized water and ethanol 3 times each, and then vacuum dry it at 60℃ for 6h to obtain 2.706g of product with a yield of 93.8%.
[0077] The obtained light green powder was subjected to XRD test, and the test results were as follows: Figure 7 The XRD results show that the product is Na3V2O2(PO4)2F, with good crystallinity and high purity. The SEM test of the product is shown in the following figure. Figure 8 The SEM results show that the prepared sodium vanadium fluorophosphate crystals have regular and uniformly distributed particles, smooth surfaces, clear grain boundaries, and very few defects, indicating that the sample has high crystallinity.
[0078] The obtained product Na3V2O2(PO4)2F was made into the positive electrode, and the metal sodium sheet was used as the negative electrode. The button battery was assembled to test its charge and discharge curve. The test results are as follows Fig. 9 The test results show that the material has two discharge platforms near 4.0V and 3.60V voltages, the discharge capacity at 0.1C current density is 126.5mAh / g, and the discharge capacity at 0.2C current density is 122.3mAh / g, indicating that it has excellent electrochemical properties.
[0079] Example 4
[0080] Dissolve 1.274g of vanadium pentoxide and 0.616g of ascorbic acid in 100mL of deionized water, heat to 90°C, stir at constant temperature for 0.5h, and stop heating; add 6.552g of sodium dihydrogen phosphate dihydrate and 1g of sodium fluoride to the above solution and stir evenly; add 6.3mL of 25% ammonia water to the above mixed solution at a uniform speed, and the addition time is 10min. After that, add 100mL of methanol to the above turbid liquid at a uniform speed, and the addition time is 0.5h. After the addition is completed, a light green precipitate is obtained at the bottom layer, and the upper liquid is almost colorless, clear and transparent; wash the above precipitate with deionized water and ethanol 3 times each, and then vacuum dry it at 60°C for 8h to obtain 2.748g of product with a yield of 95.3%.
[0081] Example 5
[0082] Dissolve 1.05g of vanadium trioxide and 5mL of phosphoric acid in 100mL of deionized water; add 6.552g of sodium dihydrogen phosphate dihydrate and 1g of sodium fluoride to the above solution and stir evenly; add 6.3mL of 25% ammonia water to the above mixed solution at a uniform speed for 10min. Then, add 100mL of tert-butyl alcohol to the above turbid liquid at a uniform speed for 1h. After the addition is completed, a light green precipitate is obtained at the bottom layer, and the upper liquid is almost colorless, clear and transparent; wash the above precipitate with deionized water and ethanol 3 times each, and then vacuum dry it at 60℃ for 12h to obtain 2.8g of product with a yield of 97.1%.
[0083] Comparative Example 1
[0084] Dissolve 1.141g of vanadium sulfate in 100mL of deionized water and stir evenly to obtain a vanadium source solution; add 3.276g of sodium dihydrogen phosphate dihydrate and 0.5g of sodium fluoride to the above vanadium source solution and stir evenly; dissolve 7.098g of sodium glutamate in 100mL of deionized water, stir and dissolve evenly, and then add it to the above mixed solution at a uniform speed, and the addition time is 1h. After the addition is completed, stop stirring, and there is no obvious sedimentation phenomenon; wash the above precipitate with deionized water and ethanol 3 times each, and then vacuum dry it at 60℃ for 6h to obtain 0.307 product with a yield of 21.3%.
[0085] The obtained product was subjected to XRD test, and the test results were as follows: Fig.10 The XRD results show that the product has very poor crystallinity and is amorphous, which is obviously inconsistent with the sodium vanadium fluorophosphate phase. The SEM test of the product is shown in the following figure. Fig.11 The SEM results show that the prepared product is flocculent and has no obvious crystal morphology.
[0086] Comparative Example 2
[0087] Compared with Example 1, the only difference in this example is that the amount of ethanol added is 200 mL, and the addition method is instantaneous addition. The other operations and parameters are the same as those in Example 1. Finally, 0.79 g of product is obtained, and the yield is 54.8%. The obtained product is subjected to XRD test, and the test results are as follows: Fig.12 As shown. From the XRD results, it can be seen that the main characteristic diffraction peaks become broad and overlapped, indicating that the crystallinity of the obtained product is poor. At the same time, the obtained product was tested by SEM, and the test results are shown in Fig.13 The SEM results show that the sample particles are irregular in shape, rough in surface, with blurred grain boundaries, and there are many defects and cracks, which further proves that the sample has a low degree of crystallinity.
[0088] Comparative Example 3
[0089] Compared with Example 2, the only difference is that the anti-solvent methanol is not added, and the other operations and parameters are the same as Example 2. 0.221 g of light blue powder is obtained, and the yield is 15.3%.
[0090] Comparative Example 4
[0091] Compared with Example 5, the only difference is that the anti-solvent tert-butyl alcohol is not added, and the other operations and parameters are the same as Example 5. 0.284 g of light blue powder is obtained, with a yield of 19.7%.
[0092] It can be seen from the comparative example that when the anti-solvent is not used in the reaction system, the product crystallinity formed is extremely poor, and the vanadium conversion rate is extremely low. This is because when only the complex precipitant is involved, the initial accumulation of supersaturation in the system is insufficient, and the precipitation of sodium vanadium fluorophosphate crystals at room temperature and normal pressure cannot be effectively driven. A single complex precipitant cannot provide enough driving force to promote the nucleation and growth of crystals, resulting in low crystallinity and vanadium conversion of the product. Even if the complex precipitant and anti-solvent are introduced into the reaction system at the same time, it is hoped that the product crystallinity can be improved by the synergistic effect of the double additives, but if the ratio and addition time of the two are not appropriate, the expected effect cannot be achieved. The optimal nucleation and growth kinetics require the complex precipitant and anti-solvent to reach a suitable balance and synergistic effect in the reaction system. If the ratio is out of balance or the addition time is inappropriate, the reaction conditions cannot be fully optimized, the crystal nucleation and growth process is suppressed or uneven, resulting in a decrease in the crystallinity of the product. Therefore, it is crucial to reasonably regulate the ratio and addition time of the complex precipitant and anti-solvent. Only suitable reaction conditions can ensure that the synergistic effect between the complex precipitant and the antisolvent reaches the best state, thereby optimizing the nucleation and growth kinetics and obtaining sodium vanadium fluorophosphate crystals with high crystallinity and high vanadium conversion rate. This not only helps to improve product performance, but also improves the reliability and repeatability of the process, which is of great significance for further industrial applications.
[0093] In summary, the invention includes but is not limited to the above embodiments. Any equivalent substitution or partial improvement made under the spirit and principle of the invention shall be deemed to be within the protection scope of the invention.
Claims
1. A method for preparing a sodium vanadium fluorophosphate positive electrode material, characterized in that: The method steps include: (1) mixing a vanadium source, a sodium source, a phosphate source, a fluorine source and deionized water to obtain a mixed solution; (2) adding the complexing precipitant to the mixed solution at a uniform rate within 0.5 to 2 hours, and then adding the anti-solvent at a uniform rate within 10 to 90 minutes. After the addition is completed, the solid-liquid separation, washing, and drying are performed to obtain a sodium vanadium fluorophosphate positive electrode material; Wherein, the molar ratio of Na, V, P and F elements in the mixed solution is 3-15:2:2-15:1-15; The molar ratio of the complexing precipitant to the vanadium source is 0.5 to 5:1; The complexing precipitant is one or more of sodium glutamate, ammonia water, sodium tartrate and sodium lactate; The anti-solvent is one or more of methanol, ethanol, propanol and isopropanol; The molar ratio of the complexing precipitant to the anti-solvent is 100-250:2-5.
2. The method for preparing a sodium vanadium fluorophosphate positive electrode material according to claim 1, characterized in that: In step (1), the vanadium source includes one or more of vanadium dioxide, vanadium oxychloride, vanadium oxysulfate, vanadium trioxide and vanadium trichloride; The sodium source includes one or more of sodium fluoride, sodium dihydrogen phosphate, disodium hydrogen phosphate and sodium chloride; The phosphate source includes one or more of phosphoric acid, sodium dihydrogen phosphate, ammonium dihydrogen phosphate, disodium hydrogen phosphate and diammonium hydrogen phosphate; The fluoride source includes sodium fluoride and / or ammonium fluoride.
3. The method for preparing a sodium vanadium fluorophosphate positive electrode material according to claim 1, characterized in that: In step (2), the combination of the complex precipitant and the anti-solvent is ammonia water and isopropanol, sodium glutamate and ethanol, sodium lactate and methanol.
4. The method for preparing a sodium vanadium fluorophosphate positive electrode material according to claim 1, characterized in that: In step (2), the molar ratio of the complexing precipitant to the anti-solvent is 160-200:4-5.
5. The method for preparing a sodium vanadium fluorophosphate positive electrode material according to claim 1, characterized in that: In step (2), the complexing precipitant is added to the mixed solution at a uniform rate within 1 to 1.5 hours, and then the anti-solvent is added within 40 to 60 minutes.
6. A method for preparing a sodium vanadium fluorophosphate positive electrode material according to any one of claims 1 to 5, characterized in that: In step (2), after the anti-solvent is added, the pH value of the solution is 4 to 6.
7. A sodium vanadium fluorophosphate positive electrode material, characterized in that: It is prepared by the method described in any one of claims 1 to 7, and its chemical formula is Na3(VO 1-x PO4)2F 1+2x , where 0≤x≤1.
8. A sodium ion battery, characterized in that: It comprises a positive electrode sheet, a diaphragm, an electrolyte and a negative electrode sheet made of the sodium vanadium fluorophosphate positive electrode material described in claim 8.
9. A sodium ion battery according to claim 8, characterized in that: The separator is glass fiber; the electrolyte is an ester electrolyte; and the negative electrode sheet is a metal sodium sheet.
